Faktor Risiko Stroke pada Pasien Penyakit Ginjal Kronik di RSUP dr. Sitanala Tangerang - Delarosa, Dinda Olinda (Majalah Kedokteran Neurosains Perhimpunan Dokter Spesialis Saraf Indonesia, 2022)
Introduction: Chronic Kidney Disease (CKD) is an independent risk factor in cardiovascular disease, leading to stroke incidence. The risk of stroke increased three to seven times in CKD stage 3 to 5 compared with the general population. Risk of stroke increases when the glomerulus filtration rate (GFR) decreases. Aim: This study is to know stroke risk factors in chronic kidney disease patients, especially at RSUP Dr Sitanala. Methods: This study was descriptive-analytic, a case-control study. Data were collected from the medical record from January 2021 to November 2021 at RSUP Dr Sitanala with purposive sampling based on inclusion and exclusion criteria. Data used univariate analysis, bivariate analysis with Chi-square, and logistic regression test. Results: From 100 samples showed that ten patients experienced a stroke. Woman (6%) was higher than man (4%). Hypertension was a higher risk factor (8%). CKD stage 5 was higher (9%) than other stages. Dyslipidemia and hyperuricemia had a significant relation statistically with stroke incidents in CKD patients. Hyperuricemia increased stroke 14 times in CKD patients. Conclusion: CKD is related to stroke by considering its severity based on CKD stages, hemodialysis, and underlying risk factors management.